2021
DOI: 10.1007/s00784-021-03833-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy assessment of dynamic computer–aided implant placement: a systematic review and meta-analysis

Abstract: Objectives To assess the accuracy of dynamic computer-aided implant surgery (dCAIS) systems when used to place dental implants and to compare its accuracy with static computer-aided implant surgery (sCAIS) systems and freehand implant placement. Materials and Methods An electronic search was made to identify all relevant studies reporting on the accuracy of dCAIS systems for dental implant placement. The following PICO question was developed: "In patients or artificial models, is dental implant placement accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 61 publications
1
72
0
1
Order By: Relevance
“…Previously published data on the accuracy of dynamic navigation were analyzed in three systematic reviews. On average, the coronal 3D deviation at the implant shoulder was between 1.00 mm (95% CI 0.83, 1.16 mm) and 1.11 mm (95% CI 0.96, 1.26 mm) [ 31 , 43 , 44 ]. The implant exit point is particularly important for prosthetically predictable results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously published data on the accuracy of dynamic navigation were analyzed in three systematic reviews. On average, the coronal 3D deviation at the implant shoulder was between 1.00 mm (95% CI 0.83, 1.16 mm) and 1.11 mm (95% CI 0.96, 1.26 mm) [ 31 , 43 , 44 ]. The implant exit point is particularly important for prosthetically predictable results.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the 3D offset at the implant tip was 1.95 mm (95% CI, 1.39–2.50 mm). A safety distance of at least 2 mm, as specified for static navigation, must be observed [ 21 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing sCAIS with dCAIS, Kaewsiri et al ( 21), Mischkowski et al (22), and Block et al (36) concluded that dynamic navigation provided higher accuracy than any static guide system but without statistical significance. On the other hand, Jorba-Garcıá et al (43) considered that not all commercial dynamic systems are suitable for treating difficult fully edentulous cases, suggesting the use of static systems as the first-line option in guided implant surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, Jorba-García et al showed a mean angular deviation of 2.1° and a mean horizontal deviation of 0.46 mm at the coronal entry point for computer-aided surgery using dynamic navigation systems [ 28 ]. Xiaojun et al showed a mean horizontal deviation of 1.36 ± 0.59 mm at the coronal entry point of conventional-length dental implants [ 18 ]; Chen et al, 1.12 ± 0.29 mm [ 14 ]; Hung et al, 1.07 ± 0.15 mm [ 20 ]; Hung et al, 1.35 ± 0.75 mm [ 17 ]; Block et al, 0.4 mm [ 29 ]; Kaewsiri et al, 1.05 ± 0.44 mm [ 30 ]; and Zhou et al, 1.56 ± 0.54 mm [ 8 ].…”
Section: Discussionmentioning
confidence: 99%